Gêneros e os cadernos de língua inglesa da Secretaria de Educação de São Paulo - Araujo, Luzia Colferai (2011)
From a Vigotskian (1987/2008) socio-historic point of view language is viewed as a place of interaction and language teaching and learning takes into consideration the participants of the interaction in their specific socio-cultural context. The approach to language teaching based on the study of genres seems to agree with the vigotskian theory because when considering the fact that all kinds of communication take place through the use of genres, language teaching and learning will happen in contextualized interactive situations. The theoretical chapter of this study shows the concept of genre according to Swales (1990, 1998), the suggestion of genre analysis based on Bhatia (1993), the suggestion of a pedagogical approach for the study of genres detailed by Ramos (2004) and the suggestions contained on the official document in which the Department of Education of the State of São Paulo has proposed a new methodological direction for all State Schools called Proposta Curricular do Estado de São Paulo (2008). The corpus selected for this study can be divided into two parts: the first one documental consists of the teacher s notebook for the high school first year segundo volume da 1ª série do Ensino Médio dos Cadernos de Língua Inglesa distributed to the teachers by the São Paulo State Department of Education in 2008. The second part of the corpus consists of the answers given by a group of teachers to a questionnaire and two group interviews with the same group of participating teachers. The methods used to collect the data were the questionnaires (FLICK, 2009) and the group interviews (SEIDMAN, 1998, OPPENHEIM, 1992). This study, which can be characterized as qualitative interpretive (BASSEY, 2002, BORTONI-RICARDO, 2008, CHIZZOTTI, 2008, 1991) aims at answering the two following research questions: a) How do the activities in the notebook chosen for this study suggest the study of genres? b) What were the impressions of the teachers in relation to the distribution of the material to the schools and in relation to the suggestion for the study of genre? Data analysis reveals issues of fundamental importance that have to be reconsidered in relation to the activities proposed for the study of genres in the notebook analyzed. It also reveals issues in relation to teacher education suggesting that teachers need to be prepared to actually lead students to a real and meaningful learning of genres